1995
DOI: 10.1128/aac.39.12.2759
|View full text |Cite
|
Sign up to set email alerts
|

Absolute bioavailability and metabolic disposition of valaciclovir, the L-valyl ester of acyclovir, following oral administration to humans

Abstract: Valaciclovir (Valtrex), the L-valyl ester of acyclovir, is undergoing clinical development for the treatment and suppression of herpesviral diseases. The absolute bioavailability of acyclovir from valaciclovir and the metabolic disposition of valaciclovir were investigated with healthy volunteers in two separate studies. In a randomized, crossover study, 12 fasting healthy volunteers each received 1,000 mg of oral valaciclovir and a 1-h intravenous infusion of 350 mg of acyclovir. The mean absolute bioavailabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
163
2
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(176 citation statements)
references
References 12 publications
8
163
2
1
Order By: Relevance
“…Serum levels and area under the curve (AUC) are comparable to those achieved with intravenous acyclovir. [13][14][15] Recent prospective randomized studies using valacyclovir for the prophylactic treatment of CMV infection have shown safety and efficacy in patients with renal transplants and AIDS. [16][17][18][19] However, the benefit of this approach for CMV prophylaxis in SCT recipients has not been reported.…”
mentioning
confidence: 99%
“…Serum levels and area under the curve (AUC) are comparable to those achieved with intravenous acyclovir. [13][14][15] Recent prospective randomized studies using valacyclovir for the prophylactic treatment of CMV infection have shown safety and efficacy in patients with renal transplants and AIDS. [16][17][18][19] However, the benefit of this approach for CMV prophylaxis in SCT recipients has not been reported.…”
mentioning
confidence: 99%
“…Valacyclovir and famciclovir have superior plasma bioavailability to acyclovir as oral preparations [11]. The aim of the present study is to add to this evidence with 2 additional cases of ARN treated with valacyclovir .…”
Section: Discussionmentioning
confidence: 98%
“…The 2 g t.i.d. dose was well tolerated and neither patient developed systemic adverse effects associated with the treatment.treatment of varicella zoster acute retinal necrosis syndrome, with good anatomic and functional results [10].Valacyclovir and famciclovir have superior plasma bioavailability to acyclovir as oral preparations [11]. The aim of the present study is to add to this evidence with 2 additional cases of ARN treated with valacyclovir .…”
mentioning
confidence: 96%
“…Acyclovir valylchenodeoxycholate was designed to assess potential for hASBT targeting as against PepT1 targeting. Valacyclovir (L-valine ester prodrug of acyclovir) is an prodrug of acyclovir that has improved the oral bioavailability of acyclovir with human oral bioavailability of 54% 14,63 . Valacyclovir is a substrate for the PepT1 intestinal transporter, with a Ki=4.08 mM in PepT1 expressing Xenopus laevis oocytes 64 and Ki=1.10 mM in stable lines of CHO/PepT1 13 .…”
Section: Bile Acid Derivatives As "Trojan Horses" For Delivery Of Thementioning
confidence: 99%